2015
DOI: 10.1002/aelm.201500240
|View full text |Cite
|
Sign up to set email alerts
|

Reversing the Resistivity Contrast in the Phase‐Change Memory Material GeSb2Te4 Using High Pressure

Abstract: Phase‐change memory devices distinguish “1” and “0” states by the electrical contrast between the amorphous and the crystalline phases. Under ambient conditions, the amorphous phase normally exhibits a higher resistivity, exceeding its crystalline counterpart by 2–5 orders of magnitude. Here, however, it is demonstrated that such pronounced resistivity contrast is remarkably reduced and even reversed with increasing hydrostatic‐like pressure in the prototypical phase‐change material GeSb2Te4 (GST). This anomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 66 publications
2
25
0
Order By: Relevance
“…It has been demonstrated that the applied pressure plays an important role in influencing the crystal structure and the associated physical properties such as the resistivity contrast in the phase-change memory material GeSb 2 Te 4 . 44 The pressureinduced structural phase transition in CGT is expected to alter its electronic properties, which can be reflected by the measured resistance plotted in Figure 6(a). The resistance shows a rapid decrease for phase  within the measured pressure range.…”
Section: Electronic Transport Properties Under Extreme Conditionsmentioning
confidence: 99%
“…It has been demonstrated that the applied pressure plays an important role in influencing the crystal structure and the associated physical properties such as the resistivity contrast in the phase-change memory material GeSb 2 Te 4 . 44 The pressureinduced structural phase transition in CGT is expected to alter its electronic properties, which can be reflected by the measured resistance plotted in Figure 6(a). The resistance shows a rapid decrease for phase  within the measured pressure range.…”
Section: Electronic Transport Properties Under Extreme Conditionsmentioning
confidence: 99%
“…6 is a clear example how local distortions and the disorder of such distortions affect the band gap. On the one hand, the ordered c-GeTe (without PLD) has narrower band gap than the ordered r-GeTe by $0.34 eV, majorly because the PLD in r-GeTe opens the band gap, 16,34 and meanwhile, the so-called resonant bonding in the completely ordered c-GeTe is strengthened, leading to the small band gap. 50 On the other hand, the disordered GeTe has smaller band gap than the ordered one (all with distortion), but the difference is not signicant (0.1-0.2 eV).…”
mentioning
confidence: 99%
“…As the Peierls-like distortion (PLD) is one of the major structural features in phase change materials, [57][58][59] we also study it in the 6-fold octahedrons with different cutoff values of structure fitting scores, as shown in Figure 5. Here the PLD factor is obtained by averaging the differences of long-and short-bonds in the diagonal lines of each octahedron (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, both the distortion factors of Ge-and Sb-centered 6-fold octahedral structures concentrate at the vicinity of 0.45 Å, in line with the previous reports. 57,58 This indicates that even though the shape of octahedral clusters may vary (characterized by different structure fitting scores), the intrinsic PLD remains at the same level and thus they may equally contribute to a similar band gap. Therefore, the PLD factor derived from ACA method can effectively reflect the distortion of local structure in amorphous GST and its electronic structure.…”
Section: Resultsmentioning
confidence: 99%